2020
DOI: 10.1021/acs.cgd.0c00064
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Oil Crystallization on Tripalmitin and Tristearin Seed Crystals with Different Polymorphs

Abstract: This study evaluates the influence of the polymorphs of triacylglycerol (TAGs) seed crystals on the crystallization of coconut oil (CO) using seeding techniques. Tripalmitin (PPP) and tristearin (StStSt) with three polymorphs (α, β′, and βα forms) were used as the seed materials. β form seed crystals were prepared by transforming in the solid state from the α form (βα) and by annealing TAG powder (βann). The CO crystallization on the TAG seed crystals was observed at 20 °C using differential interference contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Epitaxial effects may be particularly feasible given the results from a recent crystal seeding study . In this study, the polymorphic crystallization of TAGs in coconut oil was controlled by using seed crystals of high-melting TAGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epitaxial effects may be particularly feasible given the results from a recent crystal seeding study . In this study, the polymorphic crystallization of TAGs in coconut oil was controlled by using seed crystals of high-melting TAGs.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial effects may be particularly feasible given the results from a recent crystal seeding study. 49 In this study, the polymorphic crystallization of TAGs in coconut oil was controlled by using seed crystals of high-melting TAGs. The seeding effects were most remarkable when the polymorphic form of these seed crystals was the same as that of the to-becrystallized TAGs (polymorph−polymorph matching).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mahisanunt et al. [ 31 ] investigated the influence of the polymorphs of seed crystals, PPP and SSS with three polymorphs (α, β′, and β forms) were used as the seed materials in CO. They observed that the polymorphic matching between seed crystals and CO induced nucleation of CO by epitaxial growth.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] When the subcell dimensions between the seeds and the fat being crystallized are well‐matched, the crystallization trends to be induced by epitaxial growth. [ 31 ] With the addition of α‐form MB, the crystallization of β‐form PS was retarded (Figure 5) due to the subcell mismatching. In contrast, BBB transforms to β form easily and promotes the β formation of PO and PS significantly (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation